The Diagnostic Performance of Pap Smear during Both Phases of the Menstrual Cycle: A Community-based Study in Southern Nigeria - Akpome Akan; Lawrence Omo-Aghoja; Ayotunde Adeyinka (Nigerian Postgraduate Medical Journal)
Background: Incidence of cervical cancer can be reduced using screening tests such as Pap smear to detect the premalignant stage of the disease. Although there has been a preference for more expensive human papillomavirus DNA testing due to its higher sensitivity, the Pap smear remains still very relevant in low-resource settings being cheaper and more readily available, hence the need to study factors influencing its performance. Objective: The objective of this study was to determine if there is a difference in the diagnostic performance of Pap smear performed during the proliferative and secretory phases of a menstrual cycle, using colposcopy as the gold standard. Materials and Methods: It was a community–based, comparative cross-sectional study conducted in Oghara, in Ethiope West Local Government Area, Delta State, Nigeria, over a 32-week period from January to July 2020. The participants had an integrated four-step procedure comprising Pap smear sample collection and colposcopy assessment performed during the proliferative and secretory phases of their menstrual cycle. Consenting participants who had an abnormal colposcopy finding during either phase of the cycle had cervical biopsy sampling. Results: There was no significant difference in the sensitivities (0.00 vs. 0.00), specificities (99.04 vs. 97.14, P = 0.300), positive predictive values (0.00 vs. 0.00), negative predictive values (93.63 vs. 94.44, P = 0.672) and accuracies (92.80 vs. 91.60, P = 0.317) of Pap smears performed at proliferative and secretory phases of menstrual cycle. Conclusion: Pap smear can be collected during either phase of a woman’s menstrual cycle.